Swahili Learners' Views on the Need for a Monolingual Swahili Pedagogical Dictionary - Mdee, James S. (Lexikos, 1970)
Swahili is a second language to many East and Central Africans, and a foreign language to its learners from Europe, America, Asia and other parts of Africa as well. Yet it lacks a monolingual Swahili learners' dictionary specifically designed for them. The paper discusses the need for a monolingual Swahili pedagogical dictionary which helps the foreigner learn the language. A pedagogical dictionary is oriented towards encoding Swahili, hence it is logical that some Swahili grammatical aspects are incorporated into the dictionary: noun class system, concordial agreements, the morphology of the language, etc. The paper is based on the premise that dictionary writing should be based on the users' needs which can be found out by consulting them through research. A research conducted in language schools where Swahili is taught as a foreign language covered eight items which the subjects were asked to respond to. These included: dictionaries they use, selection of a word list for a Swahili dictionary, treatment of verb derivatives, information categories to be entered in a dictionary and description of meaning. The research revealed the information categories that Swahili dictionary users would like to see included in a dictionary designed for them. It also showed that dictionary users know their needs and that they are very resourceful and useful to the lexicographer. They can help the dictionary maker to compile a dictionary tailored to their needs and wishes.